Blood profiles and histopathological changes of liver and kidney tissues from male sprague dawley rats treated with ethanol extracts of Clinacanthus nutans leaf - Sajjarattul Nurul Nadia Asyura,; Hamzah, Hazilawati; Mohamad Shaari, Rosly; Sithambaram, Shanmugavelu; Mohamed Mustapha, Noordin (Omics Publishing Group, 2016)
Background: Clinacanthus nutans (C. nutans) or commonly known as ‘Sabah snake grass’ or ‘Belalai Gajah’ is a widely known herb used to treat Herpes simplex virus (HPV), skin rashes and snake bite.